(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This work is devoted to bench tests of the new КМЦ-1 stone-cutting machine with a chain working body. Bench tests of the new КМЦ-1 stone cutting machine were based on methods for evaluating the efficiency of stone cutting machines and stone sawing machines. A stand has been developed and the functional operability of the main parts and assemblies of the new КМЦ-1 stone cutting machine has been determined for sawing stone blocks from the Ak-Tash and Sary-Tash limestone and Aravan-Tash limestone deposits. Experimental diagrams have been constructed and the relationship between the angular velocity of the drive sprocket ( Ïυ ) and the feed rate of the chain working body ( Ïυ ) has been determined. The rational modes of cutting natural stone of low and medium strength by the new stone-cutting machine КМЦ-1 have been determined. A comparative analysis of the average theoretical and experimental values of the main operating parameters of the КМЦ-1 stone-cutting machine has been performed. Recommendations are given for conducting industrial tests of the КМЦ-1 stone-cutting machine in deposits of small and medium-strength natural stone.